Microglia: The Brain’s First Responders - Bilbo, Staci (Cerebrum, 2017)
New knowledge about microglia is so fresh that it’s not even in the textbooks yet. Microglia are cells that help guide brain development and serve as its immune system helpers by gobbling up diseased or damaged cells and discarding cellular debris. Our authors believe that microglia might hold the key to understanding not just normal brain development, but also what causes Alzheimer’s disease, Huntington’s disease, autism, schizophrenia, and other intractable brain disorders.